Meningococcal lipopolysaccharides: virulence factor and potential vaccine component. - Verheul, A F (1993)
Lipopolysaccharides (LPS) are surface components of the outer membrane of Neisseria meningitidis. Today, 12 different types of meningococcal LPS (immunotypes) are known, of which 3 are prevalent in the western world. The differences between these immunotypes are in the oligosaccharide part of the LPS molecule and consist of small differences in the oligosaccharide structure, the amount and location of phosphoethanolamine groups, and the degree of O acetylation of individual monosaccharides. Although the differences between the various immunotypes are small, they have a profound influence on the immunochemical and immunological properties of these molecules. Furthermore, each individual strain synthesizes a number of different LPS molecules. The expression of the various components (protective epitopes) is influenced by growth conditions and growth phase. Meningococci can endogenously sialyate their LPS, which constitutes one of the mechanisms by which N. meningitidis can evade the response of the human host. Meningococcal LPS play a key role in the induction of septic shock and can probably enhance the invasiveness of meningococcal strains and shield protective epitopes. Therefore, incorporation of (detoxified) LPS or oligosaccharide components derived therefrom might be very beneficial for the efficacy of a vaccine against group B meningococci. An overview of the development of vaccines against group B meningococci is given, and the status and potential of meningococcal LPS-derived (synthetic) oligosaccharide-protein conjugate vaccines are discussed.